2014
DOI: 10.9790/5736-07212732
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ferrocene Based Organometallic Compounds & Antimicrobial Activity

Abstract: The synthesis, characterisation, spectral studies, antibacterial and fugal studies of some transition metal ions like Mn ++ , Co ++ , Ni ++ , Cu ++ , Pd ++ and Pt ++ complexes of ferrocene based Organometallic compounds have been reported. The coordinate bonding of nitrogen to the central metal atom which reduces the electron density in the both azomethine link and thus lower the-HC=Nabsorption. The elemental analysis data exhibit the formation of 1:1 [M: L] ratio with coordination number six in the all comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Ahmad et al carried out the synthesis of four newly modified Mannich bases of Lawsone that accommodated the Ferrocene units. Lawsone contains a naphthoquinone nucleus whose drug properties were already reported [132]. The biological study showed that compound 124a is the most active member among a series of four compounds that had maximum antiproliferative activity and it could be a promising lead for the development of ligands that could be used for the treatment of hormone-refractory prostate carcinomas and MDR tumors (Figure 48).…”
Section: Anticancer Activitymentioning
confidence: 89%
See 1 more Smart Citation
“…Ahmad et al carried out the synthesis of four newly modified Mannich bases of Lawsone that accommodated the Ferrocene units. Lawsone contains a naphthoquinone nucleus whose drug properties were already reported [132]. The biological study showed that compound 124a is the most active member among a series of four compounds that had maximum antiproliferative activity and it could be a promising lead for the development of ligands that could be used for the treatment of hormone-refractory prostate carcinomas and MDR tumors (Figure 48).…”
Section: Anticancer Activitymentioning
confidence: 89%
“…Nowadays, ferrocene derivatives have found their way into pharmacology as potent HIV, anti-cancer, anti-trypanosomal, antimalarial, anti-diabetic, and antiviral agents, among others. These potent ferrocenebased drugs were either prepared through organic synthesis or developed from alreadyrecommended drugs via drug reprofiling or repurposing strategies in which the structural variation of established drugs with ferrocene scaffolds was reported [131,132].…”
Section: Medicinal Applicationsmentioning
confidence: 99%